Augmented Reality Buku Cerita Anak Sebagai Media Mendongeng Pada Komunitas Bali Mendongeng Berbasis Android - I Made Adi Krisma Dinata; I Gede Harsemadi (Jurnal Bahasa Rupa, 2022)
The culture of reading fairy tale books by parents and children is very difficult to find, so it becomes a important issue in the Bali Mendongeng Community to develop media to preserve the storytelling culture. This study aims to utilize technology as a solution to solve problems regarding books as a storytelling medium. One of technologies can be used to make books into fun storytelling media for children is Augmented Reality. Therefore, an Augmented Reality-based children's story book illustration was made to make storytelling more interesting. The research development method is the Multimedia Development Life Cycle. This research resulted a story book entitled "Where did the little tiger go?", as well as an Android-based application that is capable of displaying two-dimensional animation with storytelling voices. The results of blackbox testing test show that all functions can run according to design. That Augmented Realitywill work well if the light intensity is 18 lux - 200 lux, camera angle settings are 30o - 90o, and the distance marker to camera is 30cm - 90cm. Based on results of questionnaire testing to determine respondents' opinions on application content, story book illustrations, and augmented reality animations, results are 88.76% with very good categories.